Socio-Demographic and Clinical Characteristics and Outcomes of COVID-19 Patients in Kaduna State (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
Advancing age and male sex were found to contribute to the fatal presentation and outcome of COVID-19 infection. Identifying factors associated with severity of presentation and mortality could improve management of COVID-19. A descriptive study to describe sociodemographic and clinical characteristics/profile and outcome of COVID-19 patients in Kaduna state with highest cases in Northern Nigeria was conducted to explore determinants of severity and overall mortality. A retrospective cross-sectional review of clinical records of 902 COVID-19 patients from 27th March, 2020 to 31st December, 2021 in the 4 isolation centers in the state was conducted. Data was analyzed using SPSS 26 and STATA SE 12 at P ≤ 0.05.Out of the nine-hundred and two (902) that satisfied the inclusion criteria, the majority were 40 years and below 496 (55%), mean age ± S.D was 40.1 ± 16.0. Majority were Males 524 (58.1%), Christians 494 (54.8%), and Non-southern Kaduna tribes 593 (65.7%). The duration of illness was found to be prolonged among the elderly males (9.36 ± 3.79) compared to females (8.5 ± 3.20days). Bivariate analysis revealed that age (X2 = 51.20 P=0.0001), Religion (X2 = 6.51 P=0.011), Marital status (X2 = 7.89 P=0.005), occupation (X2 = 7.80 P=0.005) and presence of comorbidities significantly affected the severity of clinical presentation and overall mortality among COVID-19 patients. Sex was only found to have an effect on severity of clinical symptoms (X2 = 9.90 P=0.002), but not overall mortality (X2 = 2.24 P=0.13). Age, religion, marital status, occupation and presence of comorbidity were predictors of worst clinical characteristics and mortality of COVID-19 in Kaduna State.
Keywords: Socio-Demographic; Clinical characteristics; Covid-19; Kaduna; Nigeria